2007
DOI: 10.1073/pnas.0610146104
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial approach for ferroelectric material libraries prepared by liquid source misted chemical deposition method

Abstract: Combinatorial approach for discovering novel functional materials in the huge diversity of chemical composition and processing conditions has become more important for breakthrough in thin film electronic and energy-conversion devices. The efficiency of combinatorial method depends on the preparation of a reliable high-density composition thin-film library. The physico-chemical properties of each sample on the library should be similar to those of the corresponding samples prepared by one-by-one conventional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 42 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…If stress impairments act mainly via an impairment of rate remapping processes, DG cells are expected to be more profoundly affected, as those cells are regarded as the central mediators of a rate remapping response, experiencing higher changes of firing rates than CA1 and CA3 (Leutgeb et al, 2005, 2007). Hence, the greater stress-induced decrease in firing rate observed in CA1 cells in the study of Kim et al (2007) during a rate remapping protocol might be a by-product of a systematic CA1/CA3 neuronal “slowdown” response after stress, rather than being specific to rate remapping process as defined by Leutgeb et al (2007). Nevertheless, the possibility that in processes which require rate remapping, stress has a higher impact under normal firing conditions cannot be excluded as our protocol did not test for those circumstances; we would assume that under more challenging conditions and thus higher hippocampal involvement stress effects would be amplified.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…If stress impairments act mainly via an impairment of rate remapping processes, DG cells are expected to be more profoundly affected, as those cells are regarded as the central mediators of a rate remapping response, experiencing higher changes of firing rates than CA1 and CA3 (Leutgeb et al, 2005, 2007). Hence, the greater stress-induced decrease in firing rate observed in CA1 cells in the study of Kim et al (2007) during a rate remapping protocol might be a by-product of a systematic CA1/CA3 neuronal “slowdown” response after stress, rather than being specific to rate remapping process as defined by Leutgeb et al (2007). Nevertheless, the possibility that in processes which require rate remapping, stress has a higher impact under normal firing conditions cannot be excluded as our protocol did not test for those circumstances; we would assume that under more challenging conditions and thus higher hippocampal involvement stress effects would be amplified.…”
Section: Discussionmentioning
confidence: 90%
“…This process is thought to underlie the mechanism for encoding episodic-like memories about events that have previously occurred within a specific context (Leutgeb et al, 2006; Colgin et al, 2008). Kim et al (2007) tested the idea of how acute stress affects those remapping processes in the CA1 region. A 2-h audiogenic stress protocol induced higher firing rate changes than during control conditions using a rate remapping protocol in CA1 place cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is not yet clear whether both of these associations are important for RNA movement or whether they have some other function. Other viruses that have a nucleolar phase such as Groundnut rosette virus (GRV; Kim et al, 2007b) have been shown to acquire a host factor, fibrillarin from the nucleolus and fibrillarin is re-localized and incorporated into a RNP that is competent for long-distance movement (Kim et al, 2007a). However, we do not see a similar re-localization of fibrillarin from the nucleolus with PMTV infections (unpublished results).…”
Section: The Enigmatic Role Of the Nucleusmentioning
confidence: 99%
“…1,2 These high throughput methods have been popularized in the biomolecular sciences, catalysis, electrochemistry, photovoltaic sciences, and other areas of materials science. [3][4][5][6][7][8][9][10][11][12] High throughput methods have three principal elements. The first is the preparation of large numbers of different materials samples that form the elements of a materials library.…”
Section: Introductionmentioning
confidence: 99%